การศึกษาสภาพและปัญหาการใช้หลักสูตรบูรณาการปรัชญาของเศรษฐกิจพอเพียงในโรงเรียนมัธยมศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาเขต 18 - สุขญาณกิจ ฐรวิชญ์; บูลภักดิ์ บุญฑริกา (An Online Journal of Education, 2018)
The objectives of study were to examine states and problems of implementing the instruction integrating sufficiency economy philosophy in secondary school under the secondary educational service area office 18. The populations were the secondary school under the secondary educational service area office 18, a total of 12 schools. The populations were principals, vice academic principals and teachers, a total of 240 persons. Rating-scale questionnaires were used to collect data Frequency, distribution, percentage, mean, and standard deviation. The findings revealed as follows the overall were at a high level. Considering each side in curriculum management found that the highest were Recruitment teachers, Curriculum analysis, The supervision and the evaluation of curriculum implementation, The provision of various facilities to the curriculum, Schedules setting, Programs advertising to the parents and communities, Learning programs planning and Providing teaching materials respectively. And Assigning teachers to teach was the lowest. The highest problem was Learning programs planning and Programs advertising to the parents and communities was the lowest problem. Learning management found that the highest were Development and use of instructional media, Planed activities, Curriculum analysis, Learning and Activities management and Measurement and Evaluation of learning respectively and Remedial teaching was the lowest. The highest problem was Measurement and Evaluation of learning and Learning and Activities management was the lowest problem.